The Black Furrow (Hekima Review, 1994)
The "Black FurroW'' (BF) is a catholic movement of inculturation born and active in Benin. Its originality lies in the collaboration of academic, scholars with African traditional Sages in the mission of the Church. My research will first focus on the actual process of this intellectual and spiritual collaboration, and secondly on the faithfulness and the relevance of the discourse produced by the 'BF' in the life of the Church and civil society of Benin.